Genome-wide characterization of the GRF transcription factors in potato (Solanum tuberosum L.) and expression analysis of StGRF genes during potato tuber dormancy and sprouting - Cui, Danni; Song, Yin; Jiang, Weihao; Ye, Han; Wang, Shipeng; Yuan, Li; Liu, Bailin (Frontiers in Plant Science, 2024)
Growth-regulating factors (GRFs) are transcription factors that play a crucial role in plant growth and development. This study identified 12 potato GRF transcription factors (StGRFs) and analyzed their physicochemical properties, phylogenetic relationships, gene structures and gene expression patterns using bioinformatics. The StGRFs ranged in length from 266 to 599 amino acids and had molecular weights ranging from 26.02 to 64.52 kDa. The majority of StGRFs possess three introns. The promoter region contains a multitude of cis-acting elements related to plant growth and development, as well as environmental stress and hormone response. All the members of the StGRF family contain conserved WRC and QLQ domains, and the sequences of these two conserved domain modules are highly conserved. Transcriptomic data indicates that StGRFs play a significant role in the growth and development of stamens, roots, young tubers, and other tissues or organs in potatoes, Additionally, few StGRFs exhibit differential expression patterns in response to Phytophthora infestans, elicitors, heat, salt, and drought stresses, as well as multiple hormone treatments. The results of the expression analysis indicate that StGRF1, StGRF2, StGRF5, StGRF7, StGRF10 and StGRF12 are involved in the process of tuber sprouting, while StGRF4 and StGRF9 may play a role in tuber dormancy. These findings offer valuable insights that can be used to investigate the function of StGRFs during potato tuber dormancy and sprouting.